Internal and external political competition - David Hugh-Jones (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
All rulers face political competition, both from rivals within their state, and from other states to which their subjects may exit. In a simple model, both kinds of competition are substitutes. Internal competition (democracy) benefits citizens by allowing them to replace rent-seeking rulers. But it also weakens these rulers' incentives to invest. External competition forces rent-seeking rulers to invest so as to prevent migration. As a result, citizens are less willing to fight for democracy, and rulers are less eager to oppose it, when external competition is high. In a panel of countries, there are fewer changes towards democracy when states have low GDP relative to their neighbours.
Keywords: D72; H77; 330; political competition; dictatorship; democracy; transitions; Politik; Institutioneller Wettbewerb; Public Choice; Diktatur; Demokratie; Politischer Wandel; Demokratisierung; Theorie